2008
DOI: 10.1634/stemcells.2007-0979
|View full text |Cite
|
Sign up to set email alerts
|

Adult Human Dental Pulp Stem Cells Differentiate Toward Functionally Active Neurons Under Appropriate Environmental Cues

Abstract: Human adult dental pulp stem cells (DPSCs) reside within the perivascular niche of dental pulp and are thought to originate from migrating cranial neural crest (CNC) cells. During embryonic development, CNC cells differentiate into a wide variety of cell types, including neurons of the peripheral nervous system. Previously, we have demonstrated that DPSCs derived from adult human third molar teeth differentiate into cell types reminiscent of CNC embryonic ontology. We hypothesized that DPSCs exposed to the app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
471
3
10

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 537 publications
(496 citation statements)
references
References 46 publications
12
471
3
10
Order By: Relevance
“…To achieve more advanced neural differentiation we produced NLCCs in NSCM I and differentiated these cells with a protocol that was recently described for neural differentiation of dental pulp stem cells (Arthur et al, 2008). After cultivation on poly-Lornithine and laminin NLCCs attached, spread and formed single cells with neuron-like morphologies (Fig.…”
Section: Neural Differentiation Of Pre-differentiated Dfcs (Second Step)mentioning
confidence: 99%
“…To achieve more advanced neural differentiation we produced NLCCs in NSCM I and differentiated these cells with a protocol that was recently described for neural differentiation of dental pulp stem cells (Arthur et al, 2008). After cultivation on poly-Lornithine and laminin NLCCs attached, spread and formed single cells with neuron-like morphologies (Fig.…”
Section: Neural Differentiation Of Pre-differentiated Dfcs (Second Step)mentioning
confidence: 99%
“…DT-MSCs have high proliferative capacity, are clonogenic in vitro, and demonstrate the ability to differentiate into many cell types such as osteoblasts, chondrocytes, adipocytes, myoblasts, endotheliocytes, and melanocytes, as well as neurons and glia (Gronthos 2000;Arthur et al 2008;Zhang et al 2008. Besides their multilineage differentiation and self-renewal capacity, DT-MSCs exhibit immunomodulatory activities and a greater cell growth ability than BM-MSCs.…”
Section: Dental Tissues-derived Mscsmentioning
confidence: 99%
“…Many studies have reported the in vitro formation of neuronal lineage cells from PDLSCs (Kadar et al 2009;Osathanon et al 2013). Particularly, it has been shown that untreated oral stem cells were able to differentiate into functional neurons upon injection into nervous system (Arthur et al 2008).…”
Section: Dental Tissues-derived Mscsmentioning
confidence: 99%
“…As a control, there was no morphological change and no immunostaining of implanted human foreskin fibroblast at same injection area. 59 Many in vitro differentiation studies and in vivo animal studies for neural differentiation of dental stem cells showed that dental stem cells have been proved to have neural differentiation capacity under proper culture condition and have inducing activity to regenerate neuronal defect by promoting host neuron's migration or self-differentiation into neurons in implanted animal. These studies suggest that there may be potential uses of dental stem cells in the field of neural tissue engineering and that these stem cells may one day be used for nerve regeneration.…”
Section: Neural Differentiation Of Dental Stem Cellsmentioning
confidence: 99%